Electronic government - a more economical way of providing services to citizens - Marković, Miroslav (Economic Outlook, 2025)
State administration is a complex system that functions in the service of citizens. Local self-government is a decentralized autonomous management system organized in narrower state territories, i.e. municipalities or cities. According to the principles of economy and efficiency, a model of electronic government has been constructed, which has a very important role in today’s times, and aspires to be the most important in the future. The e-government model operates in our country and is developing in accordance with the development of technologies and IT literacy, both of civil servants in administrative bodies and of citizens. The time of the Corona virus pandemic has shown where the advantages and disadvantages of the current state of digitalization are, but also the impetus for the accelerated development of e-government, conditioned by the impossibility of physical contact.